Indeks Massa Tubuh dan Dampak Diferensialnya terhadap Glikemia Puasa dibandingkan Glikemia Postprandial - Valiant Zahirul Azmi; Dinnisa Haura Zhafira Hidayat; Adnan Ahmad; Citra Ayu Maharani Permatasuri; Lyriestrata Anisa; Alya Zahra Sonia (Universitas Muhammadiyah Surabaya, 2026)
Obesity and abnormal body mass index (BMI) are established risk factors for type 2 diabetes mellitus. However, the association between BMI and glycemic status may vary across clinical populations, particularly among individuals enrolled in chronic disease management programs. This study aimed to assess the association between BMI category and glycemic status, measured by fasting plasma glucose (FPG) and 2-hour postprandial plasma glucose (2-h PPG), among Prolanis participants at Pasar Rebo Primary Health Center. An analytical cross-sectional study was conducted using secondary medical record data from a single predefined assessment month. Participants with complete records of sex, body weight, height, FPG, and 2-h PPG were included. BMI was classified according to the WHO Asia-Pacific criteria for descriptive analysis and collapsed into underweight, normoweight, and overweight–obese groups for inferential analysis. Glycemic status was classified into normal, prediabetic range, and diabetic range categories. The association between BMI category and glycemic status was analyzed using cross-tabulation and the Fisher–Freeman–Halton exact test. A total of 454 participants were included in the final analysis. Most participants were female (68.9%) and were classified as overweight or obese (68.5%). This study’s results show that the BMI category was not significantly associated with FPG status (p = 0.888). Diabetic-range FPG was observed in 83.2% of the underweight–normoweight group and 83.3% of the overweight–obese group. Similarly, BMI category was not significantly associated with 2-h PPG status (p = 0.159). Diabetic-range 2-h PPG was found in 46.2% of the underweight–normoweight group and 55.6% of the overweight–obese group. These findings suggest that BMI category alone may have limited ability to discriminate fasting or postprandial glycemic status among Prolanis participants. Direct glycemic monitoring remains important across BMI categories in this high-risk primary care population.